Monocytes Induce Reversible Focal Changes in Vascular Endothelial Cadherin Complex during Transendothelial Migration under Flow - Allport, Jennifer R. (The Rockefeller University Press, 2000)
The vascular endothelial cell cadherin complex (VE-cadherin, α-, β-, and γ-catenin, and p120/p100) localizes to adherens junctions surrounding vascular endothelial cells and may play a critical role in the transendothelial migration of circulating blood leukocytes. Previously, we have reported that neutrophil adhesion to human umbilical vein endothelial cell (HUVEC) monolayers, under static conditions, results in a dramatic loss of the VE-cadherin complex. Subsequent studies by us and others (Moll, T., E. Dejana, and D. Vestweber. 1998. J. Cell Biol. 140:403–407) suggested that this phenomenon might reflect degradation by neutrophil proteases released during specimen preparation. We postulated that some form of disruption of the VE-cadherin complex might, nonetheless, be a physiological process during leukocyte transmigration. In the present study, the findings demonstrate a specific, localized effect of migrating leukocytes on the VE-cadherin complex in cytokine-activated HUVEC monolayers. Monocytes and in vitro differentiated U937 cells induce focal loss in the staining of VE-cadherin, α-catenin, β-catenin, and plakoglobin during transendothelial migration under physiological flow conditions. These events are inhibited by antibodies that prevent transendothelial migration and are reversed following transmigration. Together, these data suggest that an endothelial-dependent step of transient and focal disruption of the VE-cadherin complex occurs during leukocyte transmigration.